STRATEGI MARKETING PUBLIC RELATIONS DALAM MELAKSANAKAN SPECIAL EVENT PROGRAM PAKET CLOSE USER GROUP (CUG) PT. INDOSAT TBK - Santoso, Prasetya Yoga; Riskiyanti, Triana (Universitas Prof. Dr. Moestopo (Beragama), 2014)
PT. Indosat Tbk is one of the major companies engaged in telecommunications services in Indonesia, PT. IndosatTbk is continues to innovate and strive to meet each communityâs telecommunications needs. With this, PT. IndosatTbk sees opportunities in the community, especially at companies that require fast communications for coordinationamong the people in it with make phone packs a pretty beneficial community and low cost that is Close UserGroup (CUG) package. However, a product must be socialized so that people will know this new product, then PT.Indosat Tbk made special event as one of they strategies to disseminate these product.The purpose of this research is 1). To analyze Marketing Public Relations Strategy in implementation the specialevent of CUG package program and analyze the implementation of that special event. 2). To analyze the constraintsfaced when implementing special event of CUG package program. 3). To attempt to find a solution andresolution of any obstacles or barriers that exist in special event of CUG package program ongoing or conducted.In this research the authors use the concept of Four Step Public Relations Strategic Planning by Cultip, Centerand Broom that describes the steps in making strategic planning in public relations, in addition the authors alsouse persuasive communication theory that explain how effective communication by way persuading to influenceattitudes, opinions, and behaviors and also Trilogy of strategy marketing public relations. This research usesdescriptive qualitative methodology where data collection is done with observation and indepth interviews withsources, and then study of literature.